Ācāryaśrī Ānandaśaṃkara Dhruva (Lālabhai Dalapatabhai Bhāratīya Saṃskṛti Vidyāmandira, 2010)
On the life and philosophy of Ānandaśaṅkara Bāpubhāī Dhruva, 1859-1942, Gujarati author and philosopher
Keywords: Dhruva; Ānandaśaṅkara Bāpubhāī